A multitude of CRP/FNR-like transcription proteins in Bradyrhizobium japonicum. (20th January 2006) - Mesa, S.; Hennecke, H.; Fischer, H.-M.
Abstract : In Bradyrhizobium japonicum, the nitrogen-fixing soya bean endosymbiont and facultative denitrifier, three CRP (cAMP receptor protein)/FNR (fumarate and nitrate reductase regulatory protein)-type transcription factors [FixK1, FixK2 and NnrR (nitrite and nitric oxide reductase regulator)] have been studied previously in the context of the regulation of nitrogen fixation and denitrification. The gene expression of both fixK 1 and nnrR depends on FixK2, which acts as a key distributor of the 'low-oxygen' signal perceived by the two-component regulatory system FixLJ. While the targets for FixK1 are not known, NnrR transduces the nitrogen oxide signal to the level of denitrification gene expression. Besides these three regulators, the complete genome sequence of this organism has revealed the existence of 13 additional CRP/FNR-type proteins whose functions have not yet been studied. Based on sequence similarity and phylogenetic analysis, we discuss in this paper the peculiarities of these additional factors.